Characterisation and photocatalytic activity of Ag-modified BiVO 4 catalyst under visible light irradiation. (15th March 2011) - Yin, Sheng; Li, Hua-ming; Liu, Ling; Xu, Hui; Xu, Yuan-guo; Liu, Cheng-tang
The Ag-BiVO4 photocatalysts were synthesised by impregnation/ calcination method and characterised by powder X-ray diffraction (XRD), scanning election microscope (SEM), X-ray photoelectron spectroscopy (XPS) and UV-vis diffuse reflectance spectra (DRS). The photocatalytic activities of Ag-modified BiVO4 were evaluated by N -demethylation of methylene blue (MB) under visible light irradiation (λ > 400 nm). The influence of Ag content and Ag-BiVO4 calcination temperature on the photodegradation activity was studied. The results demonstrated that the photocatalytic degradation efficiency of MB was more than 99% using Ag-BiVO4 within 3 hrs under visible light irradiation. The presence of Ag significantly enhanced the MB degradation efficiency under visible light irradiation and the optimal content of Ag was 3 wt.%. It was confirmed that the Ag-BiVO4 calcination temperature was very important for the photocatalytic activity and the highest photodegradation efficiency of MB was obtained when the calcination temperature was 100°C. The UV-vis spectral analysis showed that blue shift resulting from N -demethylation of MB occurred along with oxidative degradation.